O trabalho do professor jovem-doutor na pós-graduação: produção de conhecimento e discurso do professor - Ferreira, Luciana Rodrigues (2015)
The choosing of work of young doctors professors , as mean topic of this thesis, represents the author study about the scientific production and everyday work of professors with less than 10 years of doctoral experience, who are able to provide a differential profile in the knowledge transmission. The goal of this research is to understand the speech of the most productive young doctors professors of UFSCar, with the Productivity in Research scholarship, and linked with post-graduation programs, about their work and knowledge production. Therefore, the research identifies the process of public university expansion, especially in the post-graduation, and their influences in the professors work, in the case of UFSCar, analyzing the professors academic production and their opinion about the university work: teaching, researches, post-graduation and production. The research tries to understand in which way, the State, finally, through their promotion agencies (CAPES and CNPQ), regulates, supports and orientates the knowledge production and the work of the professor-researcher. The exposed data about the scientific production and professors testimonials were essential to the work analysis, and to the everyday dynamic presented. Among the presented results, can be considered that the young doctors professors presents intersection points in the university praxis, which leads us to design a profile about their work, whose adaptation to the way of make science reveals the contradiction imposed to the university and to the smaller and smaller place, given to the criticism intellectual. Finally, the exercise become to two contradictory speeches: the passion for the teaching work and the estrangement and pressure created for the work itself. It is clear that, in the context of the international cooperation, an strategy to promote the creation of research teams at the universities, and the high production of knowledge, have became goals in the regulation of those promotion agencies, clearly driven at the necessary speed to follow the world technological changes, and the reasons for which, Brazil should advance, being a big effort, creating capabilities and competences in strategical areas, through researches and researchers, specially young-doctors.